"Gravity" - a new simple negative pressure wound therapy self-build design for low income countries. (3rd October 2018) - Ramadhar, Abbigail J.; Abraham, Frank; McAllen, Christoph
Abstract: Negative Pressure Wound Therapy (NPWT) is prohibitively expensive at the moment and therefore not easily accessible in low-income countries. An additional problem is the requirement of consistent reliable electricity to power the devices. A new low-cost NPWT device was designed from low cost and simple materials and it can be built and operated following a simple set of instructions. The so-called Gravity device was made from parts costing just under £6 GBP (May 2016) and it creates a constant pressure of 125 mmHg. Gravity operated from 4 hours and 40 minutes up to 5 hours and 18 minutes before needing to be reset. This reset can be achieved without patient involvement. Gravity was taken to Kenya by a Doctor on 5 May 2016 to be evaluated. A NPWT device prototype was successfully made and positive feedback was received from Kenya.